A Dual Modulated Homochiral Helical Nanofilament Phase with Local Columnar Ordering Formed by Bent Core Liquid Crystals: Effects of Molecular Chirality. Issue 29 (23rd June 2016) - Li, Lin; Salamonczyk, Miroslaw; Jákli, Antal; Hegmann, Torsten
Abstract : Helical nanofilament (HNF) phases form as a result of an intralayer mismatch between top and bottom molecular halves in bent‐core liquid crystals (BC‐LCs) that is relieved by local saddle‐splay geometry. HNFs are immensely attractive for photovoltaic and chiral separation applications and as templates for the chiral spatial assembly of guest molecules. Here, the synthesis and characterization of two unichiral BC‐LCs and one racemic mixture with tris‐biphenyl‐diester cores featuring chiral ( R, R ) and ( S, S ) or racemic 2‐octyloxy aliphatic side chains are presented. In comparison to the achiral compound with linear side chains forming an intralayer modulated HNF phase (HNFmod ), synchrotron small angle X‐ray diffraction indicates that the unichiral derivatives form a dual modulated HNF phase with intra‐ as well as interlayer modulations (HNFmod2 ) suggesting a columnar local structure of the nanofilaments. Transmission electron microscopy and circular dichroism spectropolarimetry confirm that the unichiral materials exclusively form homochiral HNFs with a twist sense‐matching secondary twist. A contact preparation provides the first example of two identical chiral liquid crystal phases only differing in their handedness that do not mix and form an achiral liquid crystal phase with an entirely different structure in the contact zone. Abstract : Helical nanofilaments twist in sync forming a dual modulated, homochiral helical nanofilament phase, but only when the constituent molecules are unichiral. Left‐handed nanofilaments form a left‐handed, right‐handed nanofilaments a right‐handed secondary twist. The two phases with opposite handedness do not mix by forming a chiral conglomerate, as their achiral molecular counterparts, but rather induce a short correlated crystalline ribbon phase.